2023
DOI: 10.1371/journal.pone.0283303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum freeze drying and hot air drying on dried mulberry fruit quality

Abstract: Two different drying methods (vacuum freeze-drying and hot-air drying) were used to dry mulberry of three varieties ’Baiyuwang’(D1), ’Longsang’(D2) and ’Zhongshen.1’(D3), and the fresh fruit of each variety was used as the control. The effects of different processing conditions on the physical characteristics, nutrients, functional components and antioxidant activity of mulberry fruit were analyzed. The results show that after different drying methods, after vacuum freeze-drying, the physical properties of dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The freeze−dried samples had significantly higher levels of fatty acids compared to the air−dried samples. Freeze drying is more effective in preserving the nutritional content and functional components of fruits compared to air drying [ 52 ]. Freeze drying retains more fatty acids in fruits compared to air drying.…”
Section: Resultsmentioning
confidence: 99%
“…The freeze−dried samples had significantly higher levels of fatty acids compared to the air−dried samples. Freeze drying is more effective in preserving the nutritional content and functional components of fruits compared to air drying [ 52 ]. Freeze drying retains more fatty acids in fruits compared to air drying.…”
Section: Resultsmentioning
confidence: 99%
“…Without water present, some phytochemicals, including some isomers of chlorogenic acid, may be more susceptible to degradation and oxidation pathways. Additionally, cell disruption during freezing and dehydration can expose the phytochemicals to endogenous plant enzymes that remain active even after freeze-drying, potentially leading to enzymatic breakdown of these compounds [ 18 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The leaves were deep green and had flat surfaces without burnt flavor and bubbles, thus exhibiting the best quality. Wang Li et al [7] discussed the effects of the infiltration dehydration of mulberry before drying on the drying kinetics. Their results showed that the drying rate and water diffusion rate declined due to infiltration dehydration, while the internal resistance against the external diffusion of water increased.…”
Section: Introductionmentioning
confidence: 99%